Peer Groups in Supporting High School Students' Communication and Interaction - Angga Nafis Budikusuma; Ariandika Nur Asyifa; Suparmi (Konsultan Jurnal Ilmiah Indonesia, 2026)
This article examines the fundamental role of peers in students' social development at school and highlights the importance of guidance and counseling services to support the improvement of their interactions. The background of the problem includes high rates of aggressive behavior such as bullying and suboptimal interpersonal communication skills in students, which can potentially hinder social adjustment and academic achievement. The purpose of this study is to present a systematic review of the effectiveness of interventions to help students interact, specifically group learning services, in increasing positive interactions among students. The method used was a literature review of various scientific articles and research findings, including guidance actions in guidance and counseling and correlational studies focusing on peer relationships at the high school level. The results showed that group guidance interventions proved significant in various aspects, ranging from communication skills and learning motivation to social etiquette and reducing deviant behavior such as bullying. The correlational study also confirmed the relationship between interpersonal communication and student trust. The conclusion of this review is that every student needs group guidance assistance, which is an effective and practical strategy for guidance and counseling teachers to create a healthy, cooperative, and constructive interaction environment in schools.